2007
DOI: 10.1101/gad.417707
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insights and identification of two novel factors in the C. elegans NMD pathway

Abstract: The nonsense-mediated mRNA decay (NMD) pathway selectively degrades mRNAs harboring premature termination codons (PTCs). Seven genes (smg-1-7, for suppressor with morphological effect on genitalia) that are essential for NMD were originally identified in the nematode Caenorhabditis elegans, and orthologs of these genes have been found in several species. Whereas in humans NMD is linked to splicing, PTC definition occurs independently of exon boundaries in Drosophila. Here, we have conducted an analysis of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
187
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(194 citation statements)
references
References 62 publications
5
187
0
Order By: Relevance
“…We found that all 83 RNAi clones identified above elevated the expression level of PTCx, in a magnitude similar to smgl-1 (Fig. 5H and 5I) (Longman et al, 2007). Thus, the identified 83 RNAi clones appear to suppress the degradation of PTC containing mRNAs in a gene-nonspecific manner.…”
Section: © Higher Education Press and Springer-verlag Berlin Heidelbementioning
confidence: 59%
See 3 more Smart Citations
“…We found that all 83 RNAi clones identified above elevated the expression level of PTCx, in a magnitude similar to smgl-1 (Fig. 5H and 5I) (Longman et al, 2007). Thus, the identified 83 RNAi clones appear to suppress the degradation of PTC containing mRNAs in a gene-nonspecific manner.…”
Section: © Higher Education Press and Springer-verlag Berlin Heidelbementioning
confidence: 59%
“…We further examined the effect of the identified 83 RNAi clones on the expression of a previously characterized NMD target, PTCx (Longman et al, 2007). The PTCx reporter contains a GFP::LacZ fusion gene that is driven by a ubiquitous expressed promoter and a PTC is placed in the first exon of lacZ (lacZ containing four synthetic introns) (Longman et al, 2007).…”
Section: © Higher Education Press and Springer-verlag Berlin Heidelbementioning
confidence: 99%
See 2 more Smart Citations
“…Such surveys have identified proteins that regulate longevity/ageing [37][38][39][40][41][42], fat metabolism [43], transposon silencing [44], the DNA damage response [45], pronuclear migration during fertilization [46], germ cell apoptosis [47], co-suppression [48], the nonsensemediated mRNA decay pathway [49], RNAi [50] and those that protect against mutation [51]. Two other recent studies that address the regulation of cell migration and axon guidance are discussed here.…”
Section: General Surveysmentioning
confidence: 99%